Estudo das vari??veis ventilat??rias, marcadores inflamat??rios e capacidade funcional em mulheres submetidas a cirurgia bari??trica - Souza, Fabiana Sobral Peixoto (2014)
Background: Obesity is a public health problem. The imbalance between pro- and anti-inflammatory mechanisms is responsible for chronic inflammation of low grade. Besides multiple morbidities associated with obesity, these individuals have respiratory dysfunction and changes in functional capacity which reflects the physical capacity. Objectives: To investigate the impact of weight loss induced by bariatric surgery in pulmonary function, respiratory muscle strength (RMS) and in systemic and pulmonary inflammatory markers of obese women without changes in pulmonary function; to evaluate the reproducibility of the incremental shuttle walk test (ISWT) in women with morbid obesity; to assess functional capacity and oxygen consumption through ISWT in women undergone bariatric surgery. Methods: Three studies were performed, two longitudinals and one cross in which morbid obesity women were evaluated. It were conducted anthropometric measurements and body composition, lung volume and capacity data, maximal respiratory pressures, dosages of systemic and pulmonary inflammatory markers and functional capacity evaluation. Results: After bariatric surgery, it were observed improviment of the lung function and reduction of the inflammatory markers in the blood and induced sputum. ISWT proved to be reproducible and reliable test in women with morbid obesity and after bariatric surgery. showing an increase in distance traveled, but not oxygen consumption (VO2 peak) assessed during the test. Conclusion: Women with morbid obesity, with no change in lung function, showed improved respiratory function and respiratory and systemic inflammatory markers after weight loss induced by bariatric surgery. The application of two tests in the population of morbidly obese appears to be unnecessary because it had an excellent reproducibility. The ISWT provided useful information on functional status and physical function after weight loss induced by bariatric surgery.